Design and Analysis of a Fish-Friendly Micro Gravitational Water Vortex Power Plant (GWVPP) on Zarqa River, Jordan - Aouda Arfoa; Sadam Al-Mashakbeh; Abdullah Eial Awwad; Atef Saleh Al-Mashakbeh (IAES Indonesian Section, 2023)
The main water source of Zarqa River is the treated wastewater from As-Samra Wastewater Treatment Plant (As-Samra WWTP) which is located in Zarqa Governorate in Al-Hashimiyya on the eastern part of the river; this means year-round flowing water in the eastern part of the river. This hydro energy is wasted continuously without exploiting it to generate electricity, but when trying to implement traditional hydropower projects on the river the main problem faced is low water head and low water flow. Since a Gravitational Water Vortex Power Plant (GWVPP) is an in-stream hydropower technology that can be operated with a low hydraulic head of (0.7-5.0) m and a low flow rate of 0.5 m3/s at least; this study proposed to install an on-grid GWVPP on Zarqa River by one of the manufacturing companies to exploit hydro energy and to serve the local community by providing farmers needs of electricity. The study also determines the appropriate site for establishing the GWVPP by collecting site data in terms of head, flow, and proximity to the grid and roads by Google Earth, site visits, and making site measurements. Then one of the GWVPP manufacturers contacted which is Turbulent Company, and then GWVPP has been designed. Environmental and economic feasibility analyses were performed by using RETScreen Expert software. As a result, the research indicates that installing a GWVPP on the Zarqa River is technically, economically, and ecologically viable.